Spillover Effects of Land Port Economy: A Case Study of Huaihua International Land Port in Hunan, China - Hou, Tengteng; Lv, Lu; Shu, Xiaohui; Tian, Robert Guang (Journal of Applied Business and Economics, 2023)
Previous studies have shown that the construction and development of international land ports have a significant economic spillover effect on the neighboring regions. The construction and development of Huaihua International Land Port inevitably exerts economic spillover effects on the adjacent regions. It is necessary to analyze and predict the trend of economic data before and after the construction of the land port in the study area to evaluate accurately the role and effect of the land port in driving the economic development of the local and neighboring regions. Then, the impact of land ports as a variable is quantified by analyzing the difference between the predicted and actual results, thus providing a basis for formulating scientific policies. Local governments’ general public budget revenue (GPBR) is an important indicator to measure the economic development of a region. The paper uses the local governments’ GPBR of Huaihua International Land Port Economic Development Zone, Hecheng District, and Zhijiang Dong Autonomous County from January 2019 to June 2023. Based on this, time series decomposition and SARIMA modeling are carried out. It analyzes the impact of Huaihua International Land Port on the region and its economic spillover effect on the surrounding regions. The results found that the impact presented by the model is consistent with the actual situation. Therefore, the evaluation results have high accuracy and reliability.